DEVELOPING PROPOSED LAYOUT FOR INCREASING LINE EFFICIENCY ON BODYSHOP - Ong, Johan Oscar; Cornelia, Cornelia (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
Recently, an imbalance workstation in assembly line is one of the critical problems faced by many companies. Many researches have proposed various designs of assembly line balancing to solve this problem. This research compared straight line balancing and u-shaped line balancing which both had the same target to minimize the workstations. The result showed that u-shaped line balancing provided a better solution than the straight line balancing did in number of workstation. Straight line balancing utilized rank positional weight (RPW) whereas u-shaped line balancing utilized Critical Task Method (CTM). Significantly, u-shaped line balancing was more efficient than straight line balancing.